2009
DOI: 10.1039/b809049a
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitized production of singlet oxygen: spatially-resolved optical studies in single cells

Abstract: Singlet molecular oxygen, O(2)(a(1)Delta(g)), can be created in photosensitized experiments with sub-cellular spatial resolution in a single cell. This cytotoxic species can subsequently be detected by its 1270 nm phosphorescence (a(1)Delta(g)--> X(3)Sigma). Cellular responses to the creation of singlet oxygen can be monitored using viability assays. Time- and spatially-resolved optical measurements of both singlet oxygen and its precursor, the excited state sensitizer, reflect the complex and dynamic morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 53 publications
4
82
1
Order By: Relevance
“…In accordance with already published data, here in this study a characteristic fingerprint of singlet oxygen was detected upon excitation of TMPyP at 532 nm 27 . The quantum yield of singlet oxygen of TMPyP is ∼77%, which is high compared to other known photosensitizers, [36][37][38] like methylene blue 52% 39 or photofrin 36%. 40 Taking these facts into account, the efficient generation of singlet oxygen by TMPyP and the interaction of singlet oxygen with the energy-producing membrane area systems of bacteria led to a dissipation of the membrane potential and the striking antimicrobial effect.…”
Section: Paper Photochemical and Photobiological Sciencesmentioning
confidence: 80%
“…In accordance with already published data, here in this study a characteristic fingerprint of singlet oxygen was detected upon excitation of TMPyP at 532 nm 27 . The quantum yield of singlet oxygen of TMPyP is ∼77%, which is high compared to other known photosensitizers, [36][37][38] like methylene blue 52% 39 or photofrin 36%. 40 Taking these facts into account, the efficient generation of singlet oxygen by TMPyP and the interaction of singlet oxygen with the energy-producing membrane area systems of bacteria led to a dissipation of the membrane potential and the striking antimicrobial effect.…”
Section: Paper Photochemical and Photobiological Sciencesmentioning
confidence: 80%
“…37,38 However, the dye eventually localizes in the nucleus (Figure 3a). 22,39 Under our cell handling conditions, experiments were invariably initiated with an intracellular TMPyP distribution such as that shown in Figure 3a. Chlorins are a class of porphyrin-like compounds containing one pyrrole ring that is reduced at the β-position.…”
Section: General Characterization Of Tmpyp and Chlmentioning
confidence: 99%
“…This molecule tends to accumulate in the nucleus of cells, but an appreciable amount can still be found in the cytoplasm. 14,22,23 Time-resolved singlet oxygen phosphorescence experiments performed on D 2 O-incubated, TMPyP-containing cells yield an intracellular singlet oxygen lifetime of ~ 30-40 µs, irrespective of whether the data are recorded from the cytoplasm or the nucleus. [13][14][15][16] As expected based on the known solvent isotope effect (vide supra), this lifetime is progressively shortened for cells with an increasing ratio of intracellular H 2 O to D 2 O, and extrapolates to a value of ~ 3 µs in an H 2 O-containing cell.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the very low quantum efficiency of radiative transition from 1 and even in living cells or bacteria. [12][13][14]17,23 At a single cell level, Kuimova et al showed a dramatic increase in intracellular viscosity upon generation of 1 O 2 using the direct luminescence detection. 10 Nevertheless, the interpretation of the luminescence signals and the respective conclusions remain challenging and sometimes puzzling, because many parameters influence the course and the meaning of such luminescence signals at the same time.…”
Section: Introductionmentioning
confidence: 99%